(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2020)
By Virtue To The Order Number 02/15 Dated On July 23rd, 2015 Amended And Completed To The Criminal Procedures Code, A New Procedures And Mechanisms Have Been Implemented In Order To Achieve More Efficiency In The Procedures, By Aiming To End The Lawsuit Amicably, Among These Procedures, The Follow-Up System By Penal Notice As A Mechanism Based On The Streamlining And Shortening Of Procedures Which Is Applicable On The Simple Summary Offences That Place A Heavy Burden On The Justice, Hence, It Is A System That Puts An End To The Criminal Proceedings Without Following The Ordinary Judicial Procedures. Its Efficiency Depends On Its Non-Objection; However, It Affects The Main Guarantees Prescribed To The Accused Related To The Principles Procedures Of Fair Trial Such As Adversarial Principle, Self-Defence Principle, Judicial Punishment Principle. Key Words: Penal Notice, Criminal Courts, Criminal Procedures, Criminal Courts, Criminal Proceedings.